The Dynamics of B Cell Aging in Health and Disease - de Mol, Jill; Kuiper, Johan; Tsiantoulas, Dimitrios; Foks, Amanda C. (Frontiers in Immunology, 2021)
Aging is considered to be an important risk factor for several inflammatory diseases. B cells play a major role in chronic inflammatory diseases by antibody secretion, antigen presentation and T cell regulation. Different B cell subsets have been implicated in infections and multiple autoimmune diseases. Since aging decreases B cell numbers, affects B cell subsets and impairs antibody responses, the aged B cell is expected to have major impacts on the development and progression of these diseases. In this review, we summarize the role of B cells in health and disease settings, such as atherosclerotic disease. Furthermore, we provide an overview of age-related changes in B cell development and function with respect to their impact in chronic inflammatory diseases.